Avaliação da estabilidade de cor de duas resinas compostas: influência da manipulação com luvas e envelhecimento - Faciochi, Laura Piaia (2019)
Evaluate the color stability of two composite resins, associating this with handling with procedure gloves and aging. Materials and methods: 20 specimens were made of composite resins Filtek Z350XT (3M) and Empress Direct (Ivoclar), which were divided into 4 groups (n=5): Group 1- Resin Z350XT manipulation with gloves; Group 2- Resin Z350XT trowel; Group 3- Resin Empress Direct handling with glove; Group 4- Resin Empress Direct trowel. In groups 1 and 3, the composite resin was removed from the packaging with a spatula and manipulated with latex gloves, followed by photopolymerization for 40 seconds with LED light. In groups 2 and 4, the same steps were followed, except for manipulation: the material was only removed from the package, placed in the matrix and light-cured. All specimens were submitted to finishing and polishing. The color readings of the samples with a spectrophotometer were performed before and after immersion in coffee (n=5) for 12 days. The results of color variation, translucency and whiteness were compared with 1-way Anova and Tukey's test (α=0.05). Results: All groups had ΔE above the acceptability threshold. The variation in the white index (WId) indicated that the samples became darker. For TP, all groups were below the acceptability threshold, with more opaque samples, and groups G1, G3 and G4 had values above the perceptibility threshold. Conclusion: Immersion in coffee alters the color and whiteness of composite resins, with manipulation with gloves interfering with these parameters.